Peacebuilding in rural Colombia— A collective perception of the integrated rural reform (IRR) in the department of Caquetá (Amazon) - Graser, Maximilian; Bonatti, Michelle; Eufemia, Luca; Morales, Héctor; Lana, Marcos A.; Löhr, Katharina; Sieber, Stefan (MDPI, 2020)
The 2016 peace agreement between the Government of Colombia and the FARC-EP created institutional space for an effective implementation of needed rural reforms. However, the change of power structures also contains risks, like the deterioration of natural resources and the strengthening of other armed groups. By addressing collective perceptions regarding the Integrated Rural Reform (IRR), this paper shows the consequences of the peace agreement for the rural population in the department of Caquetá. Additionally, it presents the main challenges for further departmental development. The case study approach uses both semi-structured expert interviews of rural development stakeholders in different sectors based on three sampling strands, as well as participatory observation in the field. The main findings show an increase of general physical security and (economic) interest in the department since the signing of the agreement, while the deforestation rate, homicides, and threats against social-environmental leaders were all highly increased. The study also derives recommendations of departmental actors in rural development for a more effective peace implementation process, like the change from cattle driven to a more conservational economy with agri-silviculture and ecotourism, led by local civil society. To create a stable peace, it is crucial that the current government effectively implements the IRR, while also considering departmental perceptions of sustainable development. If the implementation process and departmental recognition is not enforced sufficiently, then peace might only be possible at the cost of the Amazon and its nature.